Sistem Monitoring dan Manajemen Pakan Pakan Ternak Sapi Berbasis Web Pada PT XYZ Lampung Tengah - Sania Media Nosa; Heni Sulistiani (SMATIKA JURNAL : STIKI Informatika Jurnal, 2025)
This research discusses the design and implementation of a web-based cattle feed monitoring and management system at PT XYZ Lampung Tengah. The main problem faced is the manual recording in cattle feed management, which causes inaccuracies in feed consumption data, incorrect cost calculations, and the risk of inventory shortages or excesses. The research uses the Rapid Application Development (RAD) method in system development, which consists of four phases: Requirements Planning, RAD Design Workshop, Implementation, and Maintenance and Evaluation. The developed system has features for managing user data, feed type data, feed weight recaps, as well as generating recap and stock reports. The implementation results show that the system successfully automated the feed inventory recording process with access rights distribution between admin and user, data visualization through stock and feed expenditure graphs, and the ability to generate organized reports. In making the final report on animal feed, the admin takes up to 7 days because it adjusts warehouse data with feed expenditure records. But with this Web-based monitoring and animal feed system, the admin can present the final report on the use of feed in real-time. This system helps improve operational efficiency and the accuracy of feed usage recording at PT XYZ Lampung Tengah.